A Novel Spontaneous Mutation of the SOX10 Gene Associated with Waardenburg Syndrome Type II. (28th August 2020) - Chen, Sen; Jin, Yuan; Xie, Le; Xie, Wen; Xu, Kai; Qiu, Yue; Bai, Xue; Zhang, Hui-Min; Liu, Xiao-Zhou; Wang, Xiao-Hui; Kong, Wei-Jia; Sun, Yu
Abstract : Waardenburg syndrome (WS), also known as auditory-pigmentary syndrome, is the most common cause of syndromic hearing loss. It is responsible for 2–5% of congenital deafness. WS is classified into four types depending on the clinical phenotypes. Currently, pathogenic mutation of PAX3, MITF, EDNRB, EDN3, SNAI2, or SOX10 can cause corresponding types of WS. Among them, SOX10 mutation is responsible for approximately 15% of type II WS or 50% of type IV WS. We report the case of a proband in a Chinese family who was diagnosed with WS type II. Whole exome sequencing (WES) of the proband detected a novel heterozygous spontaneous mutation: SOX10 c.246delC. According to analysis based on nucleic acid and amino acid sequences, this mutation may produce a truncated protein, with loss of the HMG structure domain. Therefore, this truncated protein may fail to activate the expression of the MITF gene, which regulates melanocytic development and plays a key role in WS. Our finding expands the database of SOX10 mutations associated with WS and provides more information regarding the molecular mechanism of WS.